Education research Australia: A changing ecology of knowledge and practice - Seddon, T.; Bennett, Dawn; Bennett, S.; Bobis, J.; Chan, P.; Harrison, N.; Shore, S. (Australian Association for Research in Education, 2013)
Processes of national research assessment, such as Excellence in Research for Australia (ERA) are a type of audit technology that confronts and steers established institutional identities and traditions. This nexus between policy and practice drives boundary work that diffracts prevailing policy logics, organisational practices, and habits of mind. We use this notion of ‘boundary work’ as an analytical lens for understanding the nature and effects of ERA in the Australian educational research space. This paper explains the methodology that informed the AARE–ACDE research reported in Strategic Capacity Building for Australian Educational Research. It documents the policy logic of ERA and the way it cuts across the established ecology of educational research, revealing social and symbolic work that is remaking the boundaries of educational research. We report on the historical trajectory of Australian educational research, the way ERA codes research outputs, and how educational researchers are repositioning in this shifting research space. We argue that there are specific loci of boundary work where capacity building in Australian educational research can make a difference to future educational knowledge building.